Effects of Metal Ratio and Promoter on Physicochemical Properties of CuFe Catalyst - Berahim, N.H. (Springer Science and Business Media B.V., 2021)
A series of CuFe catalysts have been synthesized on Al2O3 support using the impregnation method. Effects of metal ratio and potassium promoter on the physicochemical properties of these catalysts were investigated by FESEM/EDX, N2 adsorption, H2-TPR and CO2-TPD techniques. Results showed that Cu:Fe ratio and potassium promoter did not change the morphological and textural properties of the CuFe catalyst. Potassium promoter improved the reducibility and doubled the number of the medium basic sites in the CuFe catalyst. The potassium-promoted catalyst increased the CO2 conversion by a factor of four compared to that of the un-promoted CuFe catalyst. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.